Acupuncture Therapy for Cognitive Impairment: A Delphi Expert Consensus Survey - Su, Xin-Tong; Wang, Li-Qiong; Li, Jin-Ling; Zhang, Na; Wang, Lu; Shi, Guang-Xia; Yang, Jing-Wen; Liu, Cun-Zhi (Frontiers in Aging Neuroscience, 2020)
Background: Current research evidence challenges clinical decision-making when acupuncture is taken into consideration in the treatment of cognitive impairment (CI). Aiming to provide some viable recommendations for acupuncture practitioners in dealing with actual clinic issues, an expert consensus study was conducted. Methods: A clinical question investigation among 47 acupuncturists yielded 24 initial items. Subsequently, systematic reviews on acupuncture for CI were searched within 3 online databases. A panel of 30 authoritative experts were requested to respond with agreement, neutrality, or disagreement for each item. Consensus establishment was defined as the percentage of agreement on a given item > 80%. Results: Following a 2-round Delphi survey, there were 21 items reaching consensus and 3 items resulting in no consensus; of which 10 items reached 90~100% agreement, and 80~90% expert agreement was achieved for 11 items. These items could be roughly categorized into 6 domains: (1) therapeutic effects of acupuncture, (2) therapeutic principles, (3) acupoint selection and combination, (4) acupuncture parameters, (5) considerable combined therapies, and (6) possible adverse events. Conclusions: Without ready-made guideline, this expert consensus may be conducive to guide acupuncturists in implementing clinical acupuncture practice for CI. Moreover, given the lack of high-quality research evidence and plenty of unresolved clinical issues in this field, it is of necessity to carry out more studies for better clarifying the treatment algorithm.